2022
DOI: 10.12775/jehs.2022.12.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Mental resilience and professional burnout among teachers

Abstract: W artykule podjęto próbę przedstawienia zależności między prężnością psychologiczną, a wypaleniem zawodowym nauczycieli szkół podstawowych, ponadpodstawowych oraz uczelni wyższych. W pierwszej części zostały przybliżone zagadnienia prężności psychicznej oraz wypalenia zawodowego. Do przeprowadzenia badania wykorzystano Kwestionariusz Oceny Prężności (KOP-26) i Kwestionariusz LBQ, który ocenia poziom wypalenia zawodowego.  Dalsza część artykułu przedstawia wyniki badań w obszarze zależności między prężnością ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As a result, findings on protective factors of resilience in Polish teachers are rather limited. However, studies so far have found that the majority of Polish teachers report medium and high levels of resilience (Gabryś & Boczkowska, 2021; Pluskota & Zdziarski, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, findings on protective factors of resilience in Polish teachers are rather limited. However, studies so far have found that the majority of Polish teachers report medium and high levels of resilience (Gabryś & Boczkowska, 2021; Pluskota & Zdziarski, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, research on resilience and its sociodemographic correlates is so far very limited. Pluskota and Zdziarski (2022) found that elementary school teachers have significantly higher average resilience scores than high school and college teachers. The same study notes that satisfying family relationships are positively related to resilience.…”
Section: Introductionmentioning
confidence: 99%